The epidemiology of sport-related concussion: What the rehabilitation clinician needs to know - Gardner, A. J.; Quarrie, K. L.; Iverson, G. L. (Journal of Orthopaedic & Sports Physical Therapy, 2019)
Sport-related concussion is common in full-contact and collision sports. Epidemiology studies use different types of surveillance systems and concussion definitions. Concussion incidence rates vary across age, sex, sport, and level of competition. Incidence rates are increasing, likely due to higher rates of reporting following improved knowledge and increased regulations. In this review, we summarize 7 key concepts related to concussion epidemiology: concussion definition, changes in concussion knowledge, reliability and accuracy of injury surveillance systems, conservative management and return to play, reliability of self-report, incidence of concussion across levels of play, and understanding the behaviors of players, coaches, and medical personnel from a multidisciplinary management perspective.